P.023 Clinical spectrum of epilepsy associated with polymicrogyria and candidacy for surgical management. (17th June 2016) - Mai, LM; Steven, DA; Parrent, AG; Mirsattari, SM; Burneo, JG
Abstract : Background: Polymicrogyria (PMG), a malformation of cortical development, describes an area of cerebral cortex with excessively small convolutions. This study examines the clinical spectrum of epilepsy associated with PMG, a condition which commonly presents as medically-refractory epilepsy. Methods: All patients investigated in the Epilepsy Monitoring Unit from 2006 to 2015 at our centre and identified to have PMG by MRI were studied by retrospective chart review. Results: We identified 8 patients (4 male), mean age 33 years (range: 28 to 46). Seven had childhood onset of epilepsy. All experienced focal-onset seizures; 6 had occasional evolution to generalized, bilaterally convulsive seizures. PMG was associated with schizencephaly in 3 cases. Five patients were investigated with intracranial electrodes. Two patients underwent resective surgery, 1 achieved seizure-freedom, and 1 had class III (ILAE classification) following parietal corticectomy. Two patients underwent placement of vagus nerve stimulation and one a stimulator of the anterior nuclei of the thalami. Conclusions: Medically-refractory cases of PMG should be considered for presurgical evaluation, despite only a small portion being amenable to resective surgery. Extensive cortical malformation on MRI made intracranial electrodes necessary to identify the epileptic zone. Epilepsy surgery remains an important consideration given the possibility of seizure-freedom, as achieved in our patient.